2017
DOI: 10.1111/nyas.13572
|View full text |Cite|
|
Sign up to set email alerts
|

Bone quality changes associated with aging and disease: a review

Abstract: Bone quality encompasses all the characteristics of bone that, in addition to density, contribute to its resistance to fracture. In this review, we consider changes in architecture, porosity and composition, including collagen structure, mineral composition and crystal size. These factors all are known to vary with tissue and animal ages, and health status. Bone morphology and presence of micro-cracks which also contribute to bone quality, will not be discussed in this review. Correlations with mechanical perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 106 publications
2
74
0
1
Order By: Relevance
“…This is paradoxical because obesity is associated with normal or increased bone mass and is traditionally thought to be protective against fragility fractures because of higher bone mass caused by increased mechanical loading on the skeleton and higher estrogen levels (Wardlaw, 1996). Obesity is associated with increased bone marrow adipose tissue (BMAT) that alters bone marrow (BM) composition and thus may change bone architecture and bone material properties that contribute to reduced bone quality (Ambrosi et al, 2017;Boskey and Imbert, 2017;Naveiras et al, 2009;Rubin et al, 2007). However, the cellular mechanisms underlying these changes are not known.…”
Section: Introductionmentioning
confidence: 99%
“…This is paradoxical because obesity is associated with normal or increased bone mass and is traditionally thought to be protective against fragility fractures because of higher bone mass caused by increased mechanical loading on the skeleton and higher estrogen levels (Wardlaw, 1996). Obesity is associated with increased bone marrow adipose tissue (BMAT) that alters bone marrow (BM) composition and thus may change bone architecture and bone material properties that contribute to reduced bone quality (Ambrosi et al, 2017;Boskey and Imbert, 2017;Naveiras et al, 2009;Rubin et al, 2007). However, the cellular mechanisms underlying these changes are not known.…”
Section: Introductionmentioning
confidence: 99%
“…One consequence of advances in modern medicine is an ageing global population and a concomitant increase in age-related conditions. Peak bone mass is typically reached in early adulthood, after which, bone quantity and quality decline with advancing years (Riggs & Melton 1986, Boskey & Imbert 2017. Osteoporosis is a prevalent skeletal disorder characterised by reduced bone strength with an associated increased risk of fracture (NIH Consensus Development Panel on Osteoporosis Prevention and Therapy 2001), and approximately 1 in 5 men and 1 in 3 women aged over 50 years will experience a fragility fracture in their remaining lifetime (Cooper & Ferrari 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, using genome-wide association studies (GWASs), the PRDM6 gene has been shown to affect multiple, apparently unrelated inherited traits, including bone density and body mass index; therefore, it was regarded as a potentially pleiotropic gene [12,13]. The formation of the skeleton is part of the early development of an organism [14,15]. Hu et al found that the PRDM6 mutation was associated with bone development, bone density, and body mass index [12].…”
Section: Introductionmentioning
confidence: 99%